2021
DOI: 10.3389/fped.2021.640028
|View full text |Cite
|
Sign up to set email alerts
|

Field-Based Health-Related Physical Fitness Tests in Children and Adolescents: A Systematic Review

Abstract: Physical fitness (PF) is a multi-component construct and a biomarker of health. Worse PF is related to vulnerability and predicts worse academic achievements. Thus, assessing PF is important to monitor health in youth. This systematic review aimed to identify and inform physical education, health professionals and entities about existing PF batteries and field-tests that can be used in school settings. A comprehensive literature search was carried out in five electronic databases (Academic Search Complete, Edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…In this study, the CST significantly improved their standing long jump and vertical jump performance in two tests compared with the CON. The standing long jump and the vertical jump field-tests are typically used to evaluate lower body explosive muscular strength in children and adolescents[ 62 ]. Previous studies utilizing strength training in secondary school PE lessons have found that the lower body muscle strength improves.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the CST significantly improved their standing long jump and vertical jump performance in two tests compared with the CON. The standing long jump and the vertical jump field-tests are typically used to evaluate lower body explosive muscular strength in children and adolescents[ 62 ]. Previous studies utilizing strength training in secondary school PE lessons have found that the lower body muscle strength improves.…”
Section: Discussionmentioning
confidence: 99%
“…Males have higher overall physical fitness z-score values [ 13 ] and better performance compared with females, especially in testing items or sports events related to the strength of lower extremity, speed and endurance (muscle strength, ankle moment/power, dynamic stability, running economy, sprint performance, etc.) [ 14 , 15 , 16 ] Physical function plays an important role in overall health [ 17 ]; thus, the mechanism that causes gender difference should be studied. Whether or not the architectural and mechanical properties of the gMTU are a biomechanical mechanism of the superior physical fitness and exercise performance in males was explored in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Body composition is an important component of the health-related physical fitness of children and adolescents ( 1 , 2 ) and, therefore, deserves prominence in the prescription and monitoring of dietary and physical exercise programs. In addition, it is fundamental for the identification and monitoring of nutritional deviations ( 3 5 ).…”
Section: Introductionmentioning
confidence: 99%